Optimizing the first-line fertility treatment. (2nd September 2018) - Irani, Mohamad; Chow, Stephen; Keating, Derek; Elder, Simone; Rosenwaks, Zev; Palermo, Gianpiero
Abstract: The objective of this study was to identify sperm score thresholds to achieve satisfactory intrauterine insemination (IUI) success rates according to the response to stimulation with clomiphene citrate (CC). To minimize the confounding effect of female age, we included only CC/IUI cycles of women ≤35 years old. A total of 1, 194 CC/IUI cycles were included. Semen volume, concentration, and motility influenced the clinical pregnancy rate (CPR). Normal morphology (≥4%) was associated with a comparable CPR with 3%, 2%, and 1% normal forms (15.6%, 16.1%, 18.1%, and 13.1%, respectively). A combination of the total number of motile spermatozoa in the ejaculate before semen preparation (TM) at a threshold ≥20 × 10 6 was associated with a CPR of 17.8% compared to 4.6% for a threshold <20 × 10 6 ( p  < .001). Interestingly, the TM threshold to achieve satisfactory outcomes was lower (10 × 10 6 ) in patients who had an optimal response to CC (≥2 dominant follicles with an endometrial thickness ≥7 mm) compared to 40 × 10 6 for those who had a suboptimal response (one dominant follicle with an endometrial thickness <7 mm). In conclusion, the response to superovulation with CC determines each patient's TM threshold required for satisfactory outcomes. Couples whose TM is below the threshold may benefit from a superovulation with gonadotropins or in vitro fertilization.